IbM PENINGKATAN POTENSI EKOWISATA DI DESA JATIREJO KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR MELALUI PENGEMBANGAN OLAHAN JAMBU BIJI MERAH SEBAGAI OLEH-OLEH KHAS DESA WISATA JAMBU BIJI MERAH - Rohula Utami; Dwi Ishartani; Lia Umi Khasanah (LPPM UNS, 2017)
Ecotourism is currently growing rapidly. This type of tourism is environmentally friendly tourism that promotes the aspects of nature conservation, socio-cultural empowerment, and local community economy, as well as aspects of learning and education. Several local governments seized this opportunity, among them is Karanganyar. Jatirejo Village in Ngargoyoso Subdistrict is one of the villages in Karanganyar which developed as ecotourism destination by exploiting its local potency, that is red guava cultivation. To strengthen the image of Jatirejo Village as the Red Guava Tour Village, it needs several development strategies, among them creating a unique souvenir by utilizing local potency. In this activity is conducted red guava processed development as souvenir typical of Red Guava Tour Village. Partners coupled in this activity is SME (Small Medium Enterprise) Putra Jambu currently processing red guava fruit into ice cream and Kelompok Makmur Candi Tani who currently cultivate the red guava and process the red guava leaves into chips. Both SMEs have constraints in the form of limited production technology, resulting in inconsistent product quality, short shelf life, low production capacity and narrow marketing reach, and limited marketing. The first activities of IbM were accompanied the SMEs to prepare the Standard Operation Procedure (SOP). Introduction of packaging and improvement of labeling on red guava leaf chips also have revealed by this program. Several production equipments also introduced to the SMEs such as ice cream maker machine, automatic sealer, and ice cream distribution equipment (freezer). This program also conducted training and marketing assistance. With this activity, there is an improvement of product quality, performance efficiency improvement, and market expansion of SME Putra Jambu and Farmers Grup Candi Makmur.Keywords: ecotourism, red guava, Karanganyar, Ngargoyoso, Souvenirs